The Role of Continuous Professional Development (CPD) in Improving Nurse Competence in the Digital Era: Literature Review - Ria Desita Natalia; Regina Vidya Trias Novita (GLOBAL HEALTH SCIENCE GROUP, 2025)
Continuing Professional Development (CPD) is a critical need in the nursing profession along with the increasing complexity of health services and technological advancements. Continuing Professional Development (CPD) also has an important element in improving the competence and professionalism of nurses. This study aims to analyze scientific findings related to Continuing Professional Development (CPD) in nursing with a literature review approach based on the latest research. Data were collected from indexed journals in 2018-2024 from journals published in databases such as google scholar, PubMed, Springer and ProQuest. Screening was carried out based on inclusion criteria, namely the selected articles focused on the implementation and evaluation of Continuing Professional Development (CPD) in the context of nursing, both in the form of quantitative, qualitative, and mixed method research. The results of the study show that the CPD program plays an important role in ensuring that nurses update their skills and knowledge, support the implementation of evidence-based practices, and improve the quality of patient care. The importance of improving the competence of nurses and the quality of health services in the midst of challenges faced through professional development (CPD). Key challenges include limited resources, time, cost and access to technology. Digital transformation in CPD has been proven to increase the accessibility and flexibility of learning even though it still faces digital literacy constraints. The successful implementation of CPD requires organizational support, clear policies, and optimal use of technology. This study provides insights for the development of CPD programs that are more effective and adaptive to the needs of the digital era. Continuing Professional Development (CPD) has an important role in improving the competence of nurses and the quality of health services. By continuously updating knowledge and skills, supporting the implementation of evidence-based practices, and adapting to advances in health technology, it is able to respond to the complexity of evolving patient needs.